Case report: Spontaneous regression of extruded lumbar disc herniation with acupuncture therapy - Liang, Haiwen; Huang, Jianhao (Frontiers in Neurology, 2024)
Most patients with lumbar disc herniation (LDH) derive benefit from conservative treatment, prompting growing global interest in non-surgical approaches. Despite being recognized as one of the effective conservative therapies, there is currently limited evidence to support the sole efficacy of acupuncture in treating patients with acute extruded LDH. Here we report the case of a 52-year-old male who presented with low back pain and persistent radiating lower limb pain and numbness.Physical examination and magnetic resonance imaging (MRI) revealed an extruded LDH at the L5/S1 level, compressing the nerve root and causing severe radiculopathy symptoms. After 23 days of continuous inpatient acupuncture treatment, followed by 5 intermittent outpatient acupuncture treatment over 2 months, patient's pain and numbness was significantly alleviated and a followed-up MRI showed a remarkable regression of the extruded disc fragment. In this case, acupuncture as a monotherapy is safe and effective, but more conclusive evidence is needed.